PHASE PORTRAITS OF BERNOULLI QUADRATIC POLYNOMIAL DIFFERENTIAL SYSTEMS - Llibre, Jaume; Pereira, Weber F. [UNESP]; Pessoa, Claudio [UNESP] (Texas State Univ, 2020)
In this article we study a new class of quadratic polynomial differential systems. We classify all global phase portraits in the Poincare disk of Bernoulli quadratic polynomial differential systems in R-2.
Keywords: Bernoulli equation; Poincare disk; phase portrait